(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this paper is to test empirically, if during the period 2002-2017, the volatility of the Moroccan stock market could be linked to mimetic behavior of investors. On a sample made up of 22 firms listed on the Casablanca stock exchange, we adopted an estimate of this behavior according to the measure of cross sectional absolute deviation CSAD to show that there is no solid evidence on the presence of mimicry at least for the period considered in this study.